Commodification of Ethnicity and Religiosity in Local Communities in the Simultaneous Election of Regional Heads in Central Kalimantan - Erawati, Desi; Liadi, Fimier; Pelu, Ibnu A.S; Adiba, Syifa; Shafa, Shafa (LPPM IAIN Kudus, 2026)
This paper aimed to analyze how ethnic and religious commodification occurs in local communities during the simultaneous election of regional heads, especially in Central Kalimantan. This study employed a descriptive qualitative approach. Documentation, observation, and several supporting interviews were used in the data collection. Data analysis was carried out using the Miles and Huberman model, including the stages of data reduction, analysis, interpretation, and evaluation. The results show that ethnicity and religiosity are still used as political strategies to gain sympathy and empathy from various levels of society, both the lower middle and upper middle classes. However, these two aspects of identity are not dominant factors in shaping political preferences, suggesting a shift towards more pragmatic, issue-based considerations in the 2024 elections in Central Kalimantan.